Tadpoles of the horned frog Ceratophrys ornata exhibit high sensitivity to chlorpyrifos for conventional ecotoxicological and novel bioacoustic variables. (April 2018) - Salgado Costa, C.; Ronco, A.E.; Trudeau, V.L.; Marino, D.; Natale, G.S.
Abstract: Previous studies reported that some species of the family Ceratophryidae are able to produce sounds during premetamorphic tadpole stages. We have now determined the effects of the cholinesterase-inhibiting insecticide chlorpyrifos (CPF) on sounds emitted by tadpoles of Ceratophrys ornata . Tadpoles were exposed individually in order to evaluate the progression of effects. Effects on sound production were complemented with common ecotoxicological endpoints (mortality, behavior, abnormalities and growth inhibition). C. ornata was found to be more sensitive than other native (= 67%, 50%) and non-native species (= 75%, 100%) considering lethal and sublethal endpoints, respectively. Effects on sounds appear along with alterations in swimming, followed by the presence of mild, then severe abnormalities and finally death. Therefore, sound production may be a good biomarker since it anticipates other endpoints that are also affected by CPF. Ceratophrys ornata is a promising new model species in ecotoxicology. Graphical abstract: Image 1 Highlights: First investigation using C. ornata to assess the effects of a pollutant. Environmentally-relevant concentrations of chlorpyrifos are disrupting key behaviors. Tadpole sounds may be a good biomarker since it anticipates other endpoints. The species is more sensitive than other native and most non-native species. Abstract : Environmentally-relevant chlorpyrifos concentrations are disrupting key behaviors in C. ornata, including sound emission and locomotion.